(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
In this paper, we argue that the importance of care work and migration is undervalued and undertheorized in current understandings of the future of work. Discussions of the future of work are predominantly technocentric. Focus tends toward speculative predictions and the implications of supposedly inevitable technological advances that will lead to evolving adaptation skills and job loss. This prevailing discourse prioritises economic development and productivity, which is reinforced by institutional support at the global scale, influencing policy and practice. Although the demand for care work continues to grow globally, its meaningful inclusion in the future of work discourse is limited, and arguably effaced. We emphasise that the definition of care work is expansive, is difficult to quantify, and it cannot be easily automated. Similarly, high-income countries increasingly rely on migration flows to meet their care work needs, and in turn middle- and low-income countries rely on remittances to sustain their development and people’s livelihoods. In this paper, we offer a conceptual corrective to better situate the dense context of care work. In doing so, we draw on valuable perspectives on diverse economies, decent work and sustainable livelihoods, global care chains, and glocalisation. Incorporating well established insights from within these foci will lead to more effective discussion and a policy agenda for the future of work that takes socially just care work into consideration.